PENGARUH PERTUMBUHAN PENJUALAN DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019) - Yetty Utari; Hendra Hermain; Nurwani Nurwani (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2022)
The purpose of this research was to examine the influence Ã‚Â of sales growth and profitability on stock price partially and simultaneously. The population of this research was 13 automotive and componentas sub sector manufacturing companies listed in the Indonesia Stock Exchange in the period of 2015-2019 and samples of 6 companies by using purposive sampling technique. The data were processed by using multiple linear panel data analysis. The result of the research showed that first, sales growth had influence positive and insignificant on stock price. Secondly showed that profitability had influence positive and significant on stock price. Thirdly showed that sales growth and profitability influence significant on stock price simultaneously.